Effect of supplementary implantation of a sulcus‐fixated intraocular lens in patients with negative dysphotopsia. Issue 2 (February 2018) - Makhotkina, Natalia Y.; Dugrain, Vincent; Purchase, Daniel; Berendschot, Tos T.J.M.; Nuijts, Rudy M.M.A.
Abstract : Purpose : To evaluate whether the outcome of negative dysphotopsia treatment by implantation of a Sulcoflex intraocular lens (IOL) can be understood using individual biometry and optical modeling data. Setting : University Eye Clinic, Maastricht University Medical Centre, Maastricht, the Netherlands. Design : Retrospective case series. Methods : Patients with negative dysphotopsia were treated with supplementary implantation of a sulcus‐fixated IOL. Preoperative and postoperative ray‐tracing optical models of eyes with negative dysphotopsia were constructed in the Zemax Optic Studio program using individual biometric data. The relationship between biometric parameters, ray‐tracing data, and the course of negative dysphotopsia was evaluated. Results : The study comprised 8 patients (10 eyes). After surgery, negative dysphotopsia resolved completely in 6 eyes, partially in 2 eyes, and persisted in 2 eyes. There was no relationship between the course of negative dysphotopsia and age, IOL power, or individual biometry results other than a larger angle κ that was observed in 2 patients with persistent negative dysphotopsia after surgery. Preoperative ray‐tracing models showed a decrease in light irradiance at the periphery relative to the center of visual field. After sulcus‐fixated IOL implantation, this decrease partially resolved, in particular, for a small pupil aperture ( P < .05), and it was more prominent in patients in whom negative dysphotopsia resolved completely than in those with partial or persistent negative dysphotopsia ( P = .065 at 1.5 mm aperture). Conclusions : Of all individual biometry results, only angle κ showed a relationship with the course of negative dysphotopsia. In patient‐specific optical modeling of sulcus‐fixated IOL implantation, the increase in simulated light irradiance at the periphery was related to the course of negative dysphotopsia.